2017
DOI: 10.1177/2050312117729920
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine provides less body motion and respiratory depression during sedation in double-balloon enteroscopy than midazolam

Abstract: Objectives:Patients undergoing double-balloon enteroscopy require sedatives such as midazolam; however, patient’s body motion often hampers the outcome of double-balloon enteroscopy. Recently, dexmedetomidine has been used for endoscopic sedation and was reported to effectively reduce body motion. This study aimed to evaluate the efficacy and safety of sedation with dexmedetomidine in double-balloon enteroscopy (UMIN ID000015785).Methods:A prospective, observational study was conducted in 81 patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…We have used dexmedetomidine and pentazocine as anesthesia for endoscopic surgery for ASDH. Our results show that our anesthesia can suppress body motion and maintain respiration without intubation for about 95 minutes in line with findings from Oshima et al 15 Moreover, our anesthesia is safe for elderly patients without intraoperative or postoperative systemic complications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have used dexmedetomidine and pentazocine as anesthesia for endoscopic surgery for ASDH. Our results show that our anesthesia can suppress body motion and maintain respiration without intubation for about 95 minutes in line with findings from Oshima et al 15 Moreover, our anesthesia is safe for elderly patients without intraoperative or postoperative systemic complications.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, it is crucial to perform the surgery under safe and definite sedation and analgesia. Oshima et al 15 have reported that using dexmedetomidine for conscious sedation in enteroscopy can reduce body motion and respiratory depression more effectively than midazolam. We have used dexmedetomidine and pentazocine as anesthesia for endoscopic surgery for ASDH.…”
Section: Discussionmentioning
confidence: 99%
“…A transient increase in blood pressure in a short period of time after dexmedetomidine use may be associated with its direct activation on alpha 2 -adrenergic receptors on vascular smooth muscle cells and leading to vasoconstriction, after which blood pressure drops with dexmedetomidine acting on the locus ceruleus, inhibiting the sympathetic nervous system excitation and also increasing the vagal excitability [13,14]. In the current study, it is noteworthy that MAP was signi cantly higher in group D 1 after dexmedetomidine loading dose nish compared to the control group, whereas there were no signi cant changes in MAP in group D 2 at this timepoint, which may be related to the higher basic MAP in the group D 1 than group D 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Analgesics were additionally and repeatedly used for 7.5 mg as necessary, based on the consciousness and pain of the patient during the procedure. Dexmedetomidine (loaded at 6 μg/kg/h for 10 min and maintained at 0.4 μg/kg/h) was administered concomitantly in patients in whom sufficient sedation was not achieved using diazepam and pentazocine[ 10 ]. General anesthesia was used in child and adolescent patients.…”
Section: Methodsmentioning
confidence: 99%